Analisis Penegakan Hukum Terhadap Penyalahgunaan Narkotika yang dilakukan oleh Anggota TNI dan Polri - Arif Widodo; Setiyono; Nahdiya Sabrina (Postgraduate University of Merdeka Malang, 2025)
Drug abuse within the Indonesian National Armed Forces and the Indonesian National Police is a serious violation that impacts not only the personal honor of members, but also the stability of state security and the image of the institution. This action must be dealt with firmly in accordance with the provisions of the law, especially Law Number 35 of 2009 concerning Narcotics. The formulation of the problem in this study includes: (1) How is the law enforcement against drug abuse committed by members of the Indonesian National Armed Forces based on the Decision of Dilmil III-12 Surabaya and by members of the Indonesian National Police based on the legal process at the Malang Police; and (2) What are the obstacles in the process of law enforcement against drug abuse committed by members of the Indonesian National Armed Forces and the Indonesian National Police. This study uses an empirical legal method with an empirical juridical approach. The results of the study show that law enforcement within the Indonesian National Army is still based on Law Number 35 of 2009 and the Army Chief of Staff Telegram Letter Number ST/166/2020 dated January 20, 2020, which emphasizes strict sanctions without compromise. Meanwhile, the law enforcement process within the Indonesian National Police tends to provide room for consideration of lighter sanctions. Obstacles within the Indonesian National Armed Forces include internal factors such as a lack of legal socialization and a lack of integrated handling, as well as external factors such as limited infrastructure, geographical constraints, and individual character. Obstacles within the Indonesian National Police include internal factors such as weak legal awareness, violations of the code of ethics, and workload, while external factors include a lack of community participation, pressure on investigators, and environmental influences.